2008
DOI: 10.1007/s11663-008-9184-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling of the Main Blow in Basic Oxygen Steelmaking Using Measured Step Responses

Abstract: In the control and optimization of basic oxygen steelmaking, it is important to have an understanding of the influence of control variables on the process. However, important process variables such as the composition of the steel and slag cannot be measured continuously. The decarburization rate and the accumulation rate of oxygen, which can be derived from the generally measured waste gas flow and composition, are an indication of changes in steel and slag composition. The influence of the control variables o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…Several researchers have studied aspects of droplet behavior relevant to steelmaking including, decarburization, [1][2][3][4][5][6] droplet generation, [7][8][9][10][11][12][13][14][15][16] size distribution, [17,18] and residence time. [19] Other workers have developed models [20][21][22][23] and conducted plant trials, [24][25][26][27][28] which considered the role of droplets in the overall process kinetics. Previous work in the authors' laboratory [6] showed that droplet swelling, caused by CO formation inside the droplet, increased the droplet residence time in the slag, thereby favoring decarburization.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have studied aspects of droplet behavior relevant to steelmaking including, decarburization, [1][2][3][4][5][6] droplet generation, [7][8][9][10][11][12][13][14][15][16] size distribution, [17,18] and residence time. [19] Other workers have developed models [20][21][22][23] and conducted plant trials, [24][25][26][27][28] which considered the role of droplets in the overall process kinetics. Previous work in the authors' laboratory [6] showed that droplet swelling, caused by CO formation inside the droplet, increased the droplet residence time in the slag, thereby favoring decarburization.…”
Section: Introductionmentioning
confidence: 99%
“…For the automation of converter steelmaking, the process models, based on the statistical researches of the industrial data, the dynamic modeling using the measured step responses, the neural‐network models, are widely applied for the prediction of the main end‐blow parameters such as: End‐blow carbon and phosphorus content, and temperature. The fundamentals of all metallurgical processes are thermodynamic and kinetic processes.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of process models [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] developed to describe the kinetics of oxygen steelmaking process with an emphasis on the evolution of bath temperature, metal and slag chemistry. The details of these models are not available in the open literature and they are generally used for internal research requirements at steel plants.…”
Section: Introductionmentioning
confidence: 99%